2015
DOI: 10.1111/imm.12521
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 promotes CD1d‐mediated lipid antigen presentation by regulating a critical gene in glycosphingolipid biosynthesis

Abstract: SummaryCytokines that regulate the immune response signal through the Janus kinase / signal transducer and activation of transcription (JAK/STAT) pathway, but whether this pathway can regulate CD1d-mediated lipid antigen presentation to natural killer T (NKT) cells is unknown. Here, we found that STAT3 promotes antigen presentation by CD1d. Antigen-presenting cells (APCs) in which STAT3 expression was inhibited exhibited markedly reduced endogenous lipid antigen presentation to NKT cells without an impact on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Iyer et al demonstrated that STAT3 inhibition reduced endogenous lipid antigen presentation to NKT cells [50]. Knockdown of STAT3 led to decreased levels of uridine diphosphate (UDP) glucose ceramide glucosyltransferase, an enzyme involved in glycosphingolipid biosynthesis [50]. Moreover, CD1D levels of HEK-293 cells containing STAT3 knockdown were not deemed significantly different [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iyer et al demonstrated that STAT3 inhibition reduced endogenous lipid antigen presentation to NKT cells [50]. Knockdown of STAT3 led to decreased levels of uridine diphosphate (UDP) glucose ceramide glucosyltransferase, an enzyme involved in glycosphingolipid biosynthesis [50]. Moreover, CD1D levels of HEK-293 cells containing STAT3 knockdown were not deemed significantly different [50].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of STAT3 led to decreased levels of uridine diphosphate (UDP) glucose ceramide glucosyltransferase, an enzyme involved in glycosphingolipid biosynthesis [50]. Moreover, CD1D levels of HEK-293 cells containing STAT3 knockdown were not deemed significantly different [50]. However, it must be noted these studies used CD1d transfectants; thus, CD1d was not regulated by its natural, endogenous promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that ROCK actually promoted Ag presentation by MHC class II molecules (101). This was another example in which we have found specific cell signaling pathways that differentially regulate Ag presentation by MHC class II vs. CD1d (21, 96, 101). …”
Section: Introduction Of Cell Signaling Pathwaysmentioning
confidence: 95%
“…Here, crosslinking CD1d on colonic epithelial cells results in STAT3 activation; the transcription of the il-10 gene (by STAT3) and consequent IL-10 production controls inflammation in those cells (95). Recently, we showed that STAT3 is essential for CD1d-mediated Ag presentation, due to its ability to regulate the transcription of UDP glucose ceramide glycosyltransferase, an enzyme involved in the first step of glycosphingolipid biosynthesis—from which the natural ligands of CD1d are derived (96). The critical nature of STAT3 in the CD1d/NKT cell axis is evident in patients with loss-of-function mutations in STAT3.…”
Section: Introduction Of Cell Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation